Employment Training Programs and Acculturation of Native Peoples in Canada's Northwest Territories - Young, R.A.; McDermott, Peter (ARCTIC, 1988)
Theories of cultural diffusion and acculturation specify the conditions under which new behaviour, norms, and values are adopted. Both education and employment in modern enterprises have been identified as highly conducive to acculturation. This paper focuses on formal employment training as a possible agent of cultural change among native peoples in Canada's Northwest Territories. It analyzes all job training programs administered by governments over the 1971-83 period, presenting systematic data on them for the first time. During this period, the official Canadian government position about northern development was that the needs of indigenous peoples were to prevail over resource exploitation. At the same time, northern residents were to be offered training so that they might benefit from economic development by taking part in the expanding wage economy. Hence, officially, native peoples were to have a "choice of futures" - to be enabled to combine elements of southern and northern ways of life or to choose freely between them. But choices may be subtly shaped. Here we examine the structure rather than the explicit content of job training programs. We show that most programs operated by governments have been delivered in such a way as to stimulate rapid acculturation among trainees, by requiring relocation, the use of English, and adherence to fixed schedules. In recent years, some shift in program structure has been evident, so that the programs are delivered in a manner that better accommodates northern indigenous cultures. This raises the perennial, thorny question of whether segmented and obvious cultural contact is preferable to diffuse and co-optive interaction.Key words: Canadian North, Northwest Territories, employment training, acculturation, modernization, program implementation Mots clés: Grand Nord canadien, Territoires du Nord-Ouest, formation pour l’emploi, acculturation, modernisation, mise en application des programmes